Web-Based School Information System in Permata Hati Speacial School for Autism Manado - Tania A. Lamaluta; Chriestie E.J.C Montolalu; Aditya Lapu Kalua; Mahardika Inka Takaendengan; Vithiaz Y.G. Montolalu (PT. SNN MEDIA TECH PRESS, 2023)
This research aims to design and develop a web-based school information system for Permata Hati Autistic Special School in Manado, North Sulawesi. This information system will be an effective means to convey information about school achievements, school activities, and student creativity to parents/guardians, as well as to provide an introduction to the wider community about children who are categorized as autistic. From this information system, the school will be able to easily provide information related to school achievements, activities, and student creativities to parents/guardians through a website that can be accessed via the internet. In addition, this system will also help schools in explaining to the wider community about the introduction of children who fall into the category of autism through the website provided. This research will limit the design of information systems to the education process of autistic children and school activities carried out at the Permata Hati Special Autistic School in Manado.